THE ROLE OF LEGAL CONSCIOUSNESS IN THE MECHANISM OF LEGAL REGULATION - Hamraev Alisher Vohidovich; Kandov Bahodir Mirzayevich (Bright Mind Publishing, 2025)
In this article, approaching modern sources of legal consciousness, with the help of analysis, analysis-synthesis and other methodological methods, their role in the formation of a legal democratic state and civil society was studied, and the state was analyzed as their main subject.
Keywords: Legal consciousness, society, norm, legal state, legal state, legal culture.